Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Lingkungan Kerja terhadap Motivasi Kerja Guru Sekolah Dasar - Asim Supriadi; Saepul Ma'mun; Maman Suryaman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study explores the decline of work motivation among elementary school teachers in Cibarusah District, Bekasi Regency, attributed to weak principal leadership and an unsupportive work environment. Teacher motivation, as a key determinant of learning quality, is not only rooted in internal drives but also shaped by structural dynamics and the organizational culture of schools. The purpose of this study is to analyze the influence of principals’ leadership styles and the quality of the work environment on teacher motivation, while offering theoretical contributions and practical recommendations for education policy. Employing a quantitative approach with an ex post facto design, the research involved 130 respondents selected through stratified proportional random sampling, with data analyzed using multiple linear regression in SPSS version 25. The findings show that both variables significantly affect teacher motivation, with the work environment contributing more strongly (β = 0.531) than leadership style (β = 0.203). The study concludes that the synergy between transformative leadership and a supportive work environment represents a strategic foundation for fostering sustainable motivation. These findings may serve as a basis for developing integrative, adaptive, and evidence-based educational management models, while encouraging humanistic policies to strengthen teacher professionalism and enhance learning quality.